Искусительница, или Капкан на ялтинского жениха - Шилова Юлия (Криминальная мелодрама, 2009)
Экземпляры: ф.15 (20210210) / Инвентарный номер: 60693 / Цена: 20.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ш 59 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6